A Sociolinguistic History of Early Identities in Singapore From Colonialism to Nationalism - Chew, Phyllis Ghim-Lian.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2013)
What role does race, geography, religion, orthography and nationalism play in the crafting of identities? What are the origins of Singlish? This book offers a thorough investigation of old and new identities in Asia's most global city, examined through the lens of language.
Keywords: Applied linguistics; Ethnology; Sociolinguistics; Anthropology; Applied Linguistics; Social Anthropology; Cultural Anthropology; Sociology of Culture; Sociolinguistics; Anthropology